Intravenous injection of l-aspartic acid β-hydroxamate attenuates choroidal neovascularization via anti-VEGF and anti-inflammation. (May 2019) - Wu, Mengjuan; Liu, Yimei; Zhang, He; Lian, Meiling; Chen, Juan; Jiang, Haiyan; Xu, Ying; Shan, Ge; Wu, Shengzhou
Abstract: Choroidal neovascularization (CNV) is a hallmark of exudative age-related macular degeneration (exAMD) and a major cause of visual loss in AMD. Despite the widespread use of anti-VEGF therapy, serious adverse effects arise from repeated intravitreal injection of anti-VEGF antibodies, which warrant alternative strategy. We report herein that in a CNV murine model created by krypton red laser, intravenous injection of a serine racemase inhibitor, l-Aspartic acid β-hydroxamate (L-ABH), significantly reduced CNV at the dose 6 mg/kg on the first day before and followed by 3 mg/kg on the third day after laser injury. The CNV volumes were analyzed with isolectin GS-IB4 staining on choroidal/RPE flat mounts on the seventh day after laser injury. Injection of L-ABH did not produce negative effects on retinal function and visual behavior. To dissect the mechanism in vitro, pretreatment with L-ABH in primary RPE cultures significantly reduced production of vascular endothelial growth factor (VEGF) and macrophage chemotactic protein 1 (MCP-1) by TNFα-primed RPEs. Consistent with these observations, L-ABH pretreatment significantly attenuated macrophage migration mediated by TNFα-primed RPE. Collectively, intravenous injection of L-ABH significantly reduced CNV volumes via reducing production of VEGF and MCP-1 by inflammation-primed RPEs. Graphical abstract: We identify that intravenous injection of L-ABH significantly attenuates CNV by laser injury without negative effect on retinal function and visual behavior. The reducing effect on CNV is mediated via antagonizing VEGF and MCP-1 production by inflammation-primed RPEs.Image 1 Highlights: Intravenous injection of l-Aspartic acid β-hydroxamate (L-ABH) reduced choroidal neovascularization induced by laser injury. Intravenous injection of L-ABH did not pose negative effect on retinal function and visual behavior. Injection of L-ABH increased L-serine content and L/D-serine ratios in aqueous humor. L-ABH inhibited production of MCP-1, VEGF by inflammation-primed RPEs.